Kajian Hukum Usaha Batik Gonggong Sebagai Seragam Pegawai Negeri Sipil Kota Tanjungpinang - M. Endy Febri (Universitas Internasional Batam, 2020)
Tanjungpinang local government issued Tanjungpinang Mayor Decree Number 37 Year 2010 about the Official Uniform for Civil Servants and Non Civil Servants at Tanjungpinang Government Circle. That decree stated that Batik Gonggong was one of the official uniforms that must be used. With the decree which caused the economical rights, all the entrepreneurs should get the opportunity to compete without any discrimination. It was concluded that public participation was needed to conduct a study in determining a batik motive as the special characteristic of a place before it was determined as a law of the local government. It could be socialization or an open competition for the society or the related entrepreneurs, because that activity could cause an economical consequence for the public. Tanjungpinang local government should give a transparency guarantee and the same rights of access about business information for every micro, small and middle entrepreneur.